2021
DOI: 10.1172/jci.insight.145188
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1b/2a clinical trial of dantrolene sodium in patients with Wolfram syndrome

Abstract: Background: Wolfram syndrome is a rare endoplasmic reticulum disorder characterized by insulin-dependent diabetes mellitus, optic nerve atrophy, and progressive neurodegeneration.Although there is currently no treatment to delay, halt, or reverse the progression of Wolfram syndrome, preclinical studies in cell and rodent models suggest that therapeutic strategies targeting endoplasmic reticulum calcium homeostasis, including dantrolene sodium, may be beneficial. Methods:Based on the results from preclinical st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Perhaps surprisingly, direct β-cell stress–targeting therapies have moved forward more quickly for T1D than T2D. Developments include the use of verapamil in early T1D ( 83 ), dantrolene in Wolfram syndrome ( 84 ), and clinical trials for GLP1RA in Wolfram syndrome and TUDCA chemical chaperone in T1D. Preclinical studies in mice suggest that an inhibitor of IRE1 RNAse activity may offer protection in T1D ( 75 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps surprisingly, direct β-cell stress–targeting therapies have moved forward more quickly for T1D than T2D. Developments include the use of verapamil in early T1D ( 83 ), dantrolene in Wolfram syndrome ( 84 ), and clinical trials for GLP1RA in Wolfram syndrome and TUDCA chemical chaperone in T1D. Preclinical studies in mice suggest that an inhibitor of IRE1 RNAse activity may offer protection in T1D ( 75 ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of the study was to assess the safety and tolerability of the molecule, and the secondary objectives were to evaluate the efficacy of the treatment in improving residual pancreatic β-cell function, visual acuity, quality of life, and measures related to vision and neurological functions. The study showed that dantrolene sodium is well tolerated by Wolfram syndrome patients, but β-cell function, visual acuity, and neurological functions were not significantly improved after 6 months of treatment (Abreu et al, 2021). However, a patient subgroup analysis revealed a significant improvement in β-cell function in subjects who possessed the greatest degree of β-cell function at the baseline.…”
Section: Approved and Non-approved Orphan-designated Repurposed Drugs For Wolfram Syndromementioning
confidence: 89%
“…Since ER stress is deleterious for pancreatic β-cells and neurons, and is a hallmark of Wolfram syndrome, it has been proposed that reducing ER stress may have beneficial outcomes in this life-threatening disease. Accordingly, different ER stress-targeting approaches are being tested, for example, ER calcium stabilizers, chemical chaperones, GLP-1 analogs, and modulators of ER stress (Urano, 2016;Abreu et al, 2021;Pallotta et al, 2019).…”
Section: Molecular Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…We observed no deterioration in C-peptide secretion and OCT parameters, which are important markers of disease progression, while not observing the onset of new WS-related symptoms. Of note, also Valproate (NCT03717909) and Dantrolene (NCT02829268) are under investigation as possible therapeutic options for WS ( 37 – 40 ). WS is a rare orphan disease; consequently, this study suffers from the intrinsic limitations of the absence of a control group, a small sample size.…”
Section: Discussionmentioning
confidence: 99%